Financial Performance Analysis of Major Ports in India - A Study with Special Reference to Tuticorin Port Trust - Rajasekar, T.; Aravanan, S. (Indian Journal of Finance, 2011)
Infrastructure plays a very important role in the economic progress of the nation. 90% of the international cargo is transported by the ships. In this view, the performance of ports plays an important role in the economic development of a nation. Tuticorin Port, a natural harbour with a rich hinterland activated the development of the Port. The main objective of this paper is to analyse the financial performance of Tuticorin Port Trust (TPT). A case study methodology was used in order to collect all the information needed. The study has been done on the basis of secondary data. The secondary data used in this study was collected from the officials of the port, Administrative report of the port, Daily newspapers, Ministry of Commerce, Magazines of the port. In order to analyze the financial performance, Ratio analysis and Trend analysis were used. Major contributors to operating income of TPT were cargo handling and storage income (53% of total operating income). Overall, it may be stated that financial performance of TPT is comfortable. However, in spite of best efforts, the norms of various ratios in the context of Ports could not be obtained.